Perspektif Akademisi dan Mahasiswa Terhadap Integrasi Materi Keberlanjutan dan Digitalisasi dalam Pendidikan Akuntansi Vokasi - Widhiyanti, Santi; Arisudhana, Aditya; Sari, Padma Adriana; Akbar, Dharmawan Iqbal (Wahana Riset Akuntansi, 2025)
Purpose – This study aims to explore the integration of sustainability and digitalization aspects in accounting education, as well as to analyze the perspectives of academics and students at the State Polytechnic of Malang (Polinema).Design/methodology/approach – A qualitative case study approach was applied to the D-IV Accounting Management program, with data collected through questionnaires (involving 29 lecturers and 112 students) and Focus Group Discussions (FGD). Data analysis involved reduction, presentation, and conclusion drawing.Findings – The study indicates that integrating both aspects is crucial to enhancing curriculum relevance with modern industry demands. Sustainability is viewed as an ethical foundation for decision-making, while digitalization is key to improving efficiency and accuracy in accounting practices. However, key challenges include: (1) an overcrowded curriculum, (2) lecturers’ limited competency in technology and sustainability, (3) inadequate digital infrastructure, and (4) resistance to change. From an institutional perspective, external pressures (e.g., industry demands, global regulations) and normative pressures (professional standards) drive this integration, though internal resource gaps remain barriers. Proposed strategies include lecturer training, technology-based learning platforms, contextual case studies, and industry collaboration. This study contributes to developing adaptive accounting curricula and strengthens Institutional Theory in understanding higher education dynamics. The findings recommend a holistic approach to align accounting education with sustainable business practices and digital transformation.Originality/value –  This study aims to address a gap in the literature, which has predominantly focused on university-based academic institutions, by offering a qualitative exploration of vocational education—a sector that remains underexplored yet plays a strategic role in shaping accounting competencies that are adaptive to global challenges. By incorporating perspectives from both academics and students, this study provides fresh insights into the unique contributions and potential of vocational education in the evolving accounting landscape.Research limitations/implications – This study is limited to students of the D4 in Managerial Accounting program at Politeknik Negeri Malang, which may affect the generalizability of the findings to other vocational institutions or accounting programs. Despite this limitation, the study offers several important implications for various stakeholders in accounting education. For educational institutions, the results highlight the importance of developing internal policies that support systemic and continuous curriculum reform. Institutional support is essential to ensure that the integration of sustainability and digitalization topics moves beyond discourse and is meaningfully implemented in the learning process. Lecturers need to enhance their capacity through continuous training, particularly in digital literacy and understanding sustainability issues, so that the instructional materials they deliver align with industry needs and the evolving demands of the profession. For policymakers, there is a need to develop clearer and more operational national guidelines regarding graduate competency standards that integrate sustainability and digital technologies, especially in the context of vocational education.Keywords: Sustainability, digitalization, accounting education, curriculum, qualitative study.Article Type: Research Paper